Treatment-resistant and multi-therapy-resistant criteria for bipolar depression: consensus definition. (6th December 2018) - Hidalgo-Mazzei, Diego; Berk, Michael; Cipriani, Andrea; Cleare, Anthony J.; Florio, Arianna Di; Dietch, Daniel; Geddes, John R.; Goodwin, Guy M.; Grunze, Heinz; Hayes, Joseph F.; Jones, Ian; Kasper, Siegfried; et al.
Abstract : Background: Most people with bipolar disorder spend a significant percentage of their lifetime experiencing either subsyndromal depressive symptoms or major depressive episodes, which contribute greatly to the high levels of disability and mortality associated with the disorder. Despite the importance of bipolar depression, there are only a small number of recognised treatment options available. Consecutive treatment failures can quickly exhaust these options leading to treatment-resistant bipolar depression (TRBD). Remarkably few studies have evaluated TRBD and those available lack a comprehensive definition of multi-therapy-resistant bipolar depression (MTRBD). Aims: To reach consensus regarding threshold definitions criteria for TRBD and MTRBD. Method: Based on the evidence of standard treatments available in the latest bipolar disorder treatment guidelines, TRBD and MTRBD criteria were agreed by a representative panel of bipolar disorder experts using a modified Delphi method. Results: TRBD criteria in bipolar depression was defined as failure to reach sustained symptomatic remission for 8 consecutive weeks after two different treatment trials, at adequate therapeutic doses, with at least two recommended monotherapy treatments or at least one monotherapy treatment and another combination treatment. MTRBD included the same initial definition as TRBD, with the addition of failure of at least one trial with an antidepressant, a psychological treatment and a course of electroconvulsive therapy. Conclusions: The proposed TRBD and MTRBD criteria may provide an important signpost to help clinicians, researchers and stakeholders in judging how and when to consider new non-standard treatments. However, some challenging diagnostic and therapeutic issues were identified in the consensus process that need further evaluation and research. Declaration of interest: In the past 3 years, M.B. has received grant/research support from the NIH, Cooperative Research Centre, Simons Autism Foundation, Cancer Council of Victoria, Stanley Medical Research Foundation, MBF, NHMRC, Beyond Blue, Rotary Health, Geelong Medical Research Foundation, Bristol Myers Squibb, Eli Lilly, Glaxo SmithKline, Meat and Livestock Board, Organon, Novartis, Mayne Pharma, Servier, Woolworths, Avant and the Harry Windsor Foundation, has been a speaker for Astra Zeneca, Bristol Myers Squibb, Eli Lilly, Glaxo SmithKline, Janssen Cilag, Lundbeck, Merck, Pfizer, Sanofi Synthelabo, Servier, Solvay and Wyeth and served as a consultant to Allergan, Astra Zeneca, Bioadvantex, Bionomics, Collaborative Medicinal Development, Eli Lilly, Grunbiotics, Glaxo SmithKline, Janssen Cilag, LivaNova, Lundbeck, Merck, Mylan, Otsuka, Pfizer and Servier. A.C. has received fees for lecturing from pharmaceutical companies namely Lundbeck and Sunovion. A.J.C. has in the past 3 years received honoraria for speaking from Astra Zeneca and Lundbeck, honoraria for consulting from Allergan, Janssen, Lundbeck and LivaNova and research grant support from Lundbeck. G.M.G. holds shares in P1Vital and has served as consultant, advisor or CME speaker for Allergan, Angelini, Compass pathways, MSD, Lundbeck, Otsuka, Takeda, Medscape, Minervra, P1Vital, Pfizer, Servier, Shire and Sun Pharma. J.G. has received research funding from National Institute for Health Research, Medical Research Council, Stanley Medical Research Institute and Wellcome. H.G. received grants/research support, consulting fees or honoraria from Gedeon Richter, Genericon, Janssen Cilag, Lundbeck, Otsuka, Pfizer and Servier. R.H.M.-W. has received support for research, expenses to attend conferences and fees for lecturing and consultancy work (including attending advisory boards) from various pharmaceutical companies including Astra Zeneca, Cyberonics, Eli Lilly, Janssen, Liva Nova, Lundbeck, MyTomorrows, Otsuka, Pfizer, Roche, Servier, SPIMACO and Sunovion. R.M. has received research support from Big White Wall, Electromedical Products, Johnson and Johnson, Magstim and P1Vital. S.N. received honoraria from Lundbeck, Jensen and Otsuka. J.C.S. has received funds for research from Alkermes, Pfizer, Allergan, J&J, BMS and been a speaker or consultant for Astellas, Abbott, Sunovion, Sanofi. S.W has, within the past 3 years, attended advisory boards for Sunovion and LivaNova and has undertaken paid lectures for Lundbeck. D.J.S. has received honoraria from Lundbeck. T.S. has reported grants from Pathway Genomics, Stanley Medical Research Institute and Palo Alto Health Sciences; consulting fees from Sunovion Pharamaceuticals Inc.; honoraria from Medscape Education, Global Medical Education and CMEology; and royalties from Jones and Bartlett, UpToDate and Hogrefe Publishing. S.P. has served as a consultant or speaker for Janssen, and Sunovion. P.T. has received consultancy fees as an advisory board member from the following companies: Galen Limited, Sunovion Pharmaceuticals Europe Ltd, myTomorrows and LivaNova. E.V. received grants/ research support, consulting fees or honoraria from Abbott, AB-Biotics, Allergan, Angelini, Dainippon Sumitomo, Ferrer, Gedeon Richter, Janssen, Lundbeck, Otsuka and Sunovion. L.N.Y. has received grants/research support, consulting fees or honoraria from Allergan, Alkermes, Dainippon Sumitomo, Janssen, Lundbeck, Otsuka, Sanofi, Servier, Sunovion, Teva and Valeant. A.H.Y. has undertaken paid lectures and advisory boards for all major pharmaceutical companies with drugs used in affective and related disorders and LivaNova. He has also previously received funding for investigator-initiated studies from AstraZeneca, Eli Lilly, Lundbeck and Wyeth. P.R.A.S. has received research funding support from Corcept Therapeutics Inc. Corcept Therapeutics Inc fully funded attendance at their internal conference in California USA and all related expenses. He has received grant funding from the Medical Research Council UK for a collaborative study with Janssen Research and Development LLC. Janssen Research and Development LLC are providing non-financial contributions to support this study. P.R.A.S. has received a presentation fee from Indivior and an advisory board fee from LivaNova.